2009
DOI: 10.4055/cios.2009.1.2.81
|View full text |Cite
|
Sign up to set email alerts
|

The Increased Expression of Matrix Metalloproteinases Associated with Elastin Degradation and Fibrosis of the Ligamentum Flavum in Patients with Lumbar Spinal Stenosis

Abstract: BackgroundOne of the characteristics of spinal stenosis is elastin degradation and fibrosis of the extracellular matrix of the ligamentum flavum. However, there have been no investigations to determine which biochemical factors cause these histologic changes. So we performed the current study to investigate the hypothesis that matrix metalloproteinases (MMPs), which possess the ability to cause extracellular matrix remodeling, may play a role as a mediator for this malady in the ligamentum flavum.MethodsThe li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 26 publications
4
70
2
Order By: Relevance
“…In addition to its role in the development of microfibrils, another important role of MFAP-4 in the suppression of MMP-12 activity is illustrated both in our in vivo and in vitro analyses. In parallel with previous studies indicating that elastin-derived peptides induce the expression of various kinds of MMPs (including MMP-12) in several types of cells5253 and that UV radiation alone is sufficient to selectively degrade many elastic fiber associated proteins54, the enhancement of MFAP-4 is thought to be in charge of the suppression of MMP-12 activity as well as the promotion of microfibril formation which is essential for the organization of functional elastic fibers, resulting in the observed photoprotection.…”
Section: Discussionsupporting
confidence: 88%
“…In addition to its role in the development of microfibrils, another important role of MFAP-4 in the suppression of MMP-12 activity is illustrated both in our in vivo and in vitro analyses. In parallel with previous studies indicating that elastin-derived peptides induce the expression of various kinds of MMPs (including MMP-12) in several types of cells5253 and that UV radiation alone is sufficient to selectively degrade many elastic fiber associated proteins54, the enhancement of MFAP-4 is thought to be in charge of the suppression of MMP-12 activity as well as the promotion of microfibril formation which is essential for the organization of functional elastic fibers, resulting in the observed photoprotection.…”
Section: Discussionsupporting
confidence: 88%
“…There is some evidence that modulation of MMP activity may offer a novel therapeutic option for early LSS; our findings would be helpful in this regard. In a recent study on cultured rat Achilles tendon cells, Tsai et al 42 showed upregulated expression of MMPs 1,8,9,and 13 after incubation with ibuprofen (a common nonsteroidal anti-inflammatory drug regularly used in LSS treatment). Further studies are necessary to understand the clinical relevance of these findings, especially for LF hypertrophy.…”
Section: Discussionmentioning
confidence: 98%
“…They are coexpressed with MMPs and contribute to the regulation of their activity so that increases in TIMP levels reduce MMP activity. However, contradictory results regarding the delicate balance between MMP and TIMP expression have been reported in several pathological conditions, such as abdominal aortic aneurysms, chronic liver injury, and osteoarthritis [27][28][29]. According to Won et al, the expression of MMPs and TIMPs was significantly increased in the nucleus pulposus of diabetic rats compared with non-diabetic rats of the same ages [18].…”
Section: Discussionmentioning
confidence: 99%